Hepatic Dysfunction during Induction Chemotherapy in Children with Acute Lymphoblastic Leukemia and Lymphoblastic Lymphoma and Its Effects on Subsequent Therapy and Outcome - Nalla Anuraag Reddy; Keerthi Raj; Harsha Prasada Lashkari (Indian Journal of Medical and Paediatric Oncology)
Introduction The overall survival rate for childhood acute lymphoblastic leukemia (ALL) and lymphoblastic lymphoma (LBL) has shown tremendous growth in the recent years. Hepatic dysfunction is one of the complications seen during therapy and can add to the underlying morbidity of the disease, delay in chemotherapy, modification of drugs, and rarely fulminant hepatic failure.